COMMUNITY UTILISATION OF SUBCENTRES IN PRIMARY HEALTH CARE – AN ANALYSIS OF DETERMINANTS IN KERALA - V. M. NAIR; K. R. THANKAPPAN; R. S. VASAN AND P. S. SARMA
The determinants of utilisation of subcentre services in a random sample of 247 subcentres from three out of 14 districts of Kerala were investigated. Physical verification of the facilities was done in a subset of 90 subcentres and household surveys of 750 households were performed in the service areas of those subcentres. About 30 per cent of the beneficiaries utilised services of the subcentres during the reference period. The relationship of selected predictor variables on utilisation of the services was found out. The district in which a subcentre was physically present was found to be the most important correlate of its utilisation.